Analisis Sistem Rantai Pasok Pt. Semen Gresik (Persero) Tbk - Bahrain Boru Sinaga; Gema Alif Utama; Hesti Rafianti; Kushisa Atta Jaeba; Wiwit Afrigus (Jurnal Optimasi Sistem Industri, 2011)
The cement industry is an industry that requires a supply chain system is structured and well organized, it is influenced by several things, namely the level of demand for raw materials (raw material), resources, production processes, scheduling, transportation, supplier, allocation, distributors, retailers, product until they reach the consumer. This paper discusses the supply chain system on PT. Semen Gresik ranging from an overview of the company, Aggregate planning, process and production scheduling and logistics of PT Semen Gresik and supply chain management to pursue the relationship and coordination between the processes of other firms in the business pipelines, ranging from suppliers to give priority to current customers as well goods between the company, since most upstream to most downstream. The decision to determine the transportation used to distribute the products is very important. Selection of transport strategy used to obtain the type of transport that provides a fast time in the distribution is done by comparing the transport strategy transport using trucks and trains. Stages of the bidding process conducted by the company Semen Gresik to the winning vendor specified delivery of bidder list, create request for quotation, quotation maintain vendor, price comparison, process purchase order, payments, and evaluation.